Tuning Gate‐Opening of a Flexible Metal–Organic Framework for Ternary Gas Sieving Separation. Issue 50 (7th October 2020) - Dong, Qiubing; Zhang, Xin; Liu, Shuang; Lin, Rui‐Biao; Guo, Yanan; Ma, Yunsheng; Yonezu, Akira; Krishna, Rajamani; Liu, Gongpin; Duan, Jingui; Matsuda, Ryotaro; Jin, Wanqin; et al.
Abstract: In comparison with the fast development of binary mixture separations, ternary mixture separations are significantly more difficult and have rarely been realized by a single material. Herein, a new strategy of tuning the gate‐opening pressure of flexible MOFs is developed to tackle such a challenge. As demonstrated by a flexible framework NTU‐65, the gate‐opening pressure of ethylene (C2 H4 ), acetylene (C2 H2 ), and carbon dioxide (CO2 ) can be regulated by temperature. Therefore, efficient sieving separation of this ternary mixture was realized. Under optimized temperature, NTU‐65 adsorbed a large amount of C2 H2 and CO2 through gate‐opening and only negligible amount of C2 H4 . Breakthrough experiments demonstrated that this material can simultaneously capture C2 H2 and CO2, yielding polymer‐grade (>99.99 %) C2 H4 from single breakthrough separation. Abstract : One‐step sieving separation of a ternary gas mixture (C2 H2 /CO2 /C2 H4 ) has been realized by a flexible MOF NTU‐65. Successful separation relies on tuning the gate‐opening pressure of this flexible framework to optimize the separation performance. Under an optimized temperature, NTU‐65 adsorbed large amount of C2 H2 and CO2 but a negligible amount of C2 H4, readily producing high‐purity C2 H4 through a separation column.